2018
DOI: 10.1016/j.nicl.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-efferent tract involvement in primary lateral sclerosis and amyotrophic lateral sclerosis: A two-centre tract of interest-based DTI analysis

Abstract: BackgroundAfter the demonstration of a corticoefferent propagation pattern in amyotrophic lateral sclerosis (ALS) by neuropathological studies, this concept has been used for in vivo staging of individual patients by diffusion tensor imaging (DTI) techniques, both in `classical` ALS and in restricted phenotypes such as primary lateral sclerosis (PLS).ObjectiveThe study was designed to investigate that microstructural changes according to the neuropathologically defined ALS alteration pattern in PLS patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…On the basis of this neuroimaging study, we believe that the proposed staging scheme for ALS (Braak et al, 2013) is valid also for PBP patients, who should, as a result, receive an appropriate therapy, including the same access to health care systems and the opportunity to be enrolled in clinical trials as ALS patients. Our present findings are an analogy of the demonstration of corticofugal tract involvement in other restricted ALS phenotypes, namely, both fast progressive lower motor neuron disease (Rosenbohm et al, 2016; Müller et al, 2018a) and PLS (Müller et al, 2018b; Müller et al, 2018c).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the basis of this neuroimaging study, we believe that the proposed staging scheme for ALS (Braak et al, 2013) is valid also for PBP patients, who should, as a result, receive an appropriate therapy, including the same access to health care systems and the opportunity to be enrolled in clinical trials as ALS patients. Our present findings are an analogy of the demonstration of corticofugal tract involvement in other restricted ALS phenotypes, namely, both fast progressive lower motor neuron disease (Rosenbohm et al, 2016; Müller et al, 2018a) and PLS (Müller et al, 2018b; Müller et al, 2018c).…”
Section: Discussionsupporting
confidence: 85%
“…An unbiased whole brain-based approach demonstrated alterations (i.e., FA reductions) in multiple cerebral areas with a focus on the corticospinal tracts in these patients – similar to patients with ALS, but remarkably with an additional cluster in the pons, most probably as a correlate of the clinically prominent brainstem involvement. In vivo neuropathological staging by TOI-based DTI analysis (Kassubek et al, 2014; Kassubek et al, 2018; Müller et al, 2018a, Müller et al, 2018b, Müller et al, 2018c) demonstrated that patients with PBP showed a pattern of microstructural alterations in corticofugal tracts identical with those seen in ALS. In summary, patients with MND of the PBP phenotype showed the same tract involvement as ALS according to the proposed neuropathological staging in support of the hypothesis that PBP shares the cerebral involvement pattern with ALS and is, as such, an ALS sub-phenotype.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Particularly, PLS patients showed widespread structural and functional alterations encompassing both motor and extra-motor areas with a pattern resembling classic ALS patients (Figure 4), in line with previous studies. 5,47 By contrast, PMA patients did not show any structural or functional damage relative to healthy controls. These findings are in line with previous studies that could not demonstrate central nervous system damage in PMA patients, 6,7 even using a technique that is highly sensitive to local disruptions in the brain networks.…”
Section: A C C E P T E Dmentioning
confidence: 78%
“…To test the performance of different P values, two-sample t-tests were performed with three different P values (<0.05 [57][58][59], <0.01 [60], and <0.001 [61]). e cluster-size value was set to 50 [62][63][64][65], and three differentiated tissue maps of GM and WM were obtained and are shown in Figures 3 and 4.…”
Section: Two-sample T-testsmentioning
confidence: 99%